Factors of Job Placement, Self-Efficacy, and Interpersonal Communication on Employee Performance at PT. Alima Usaha Samudera Shipyard Bulang Tanjungpinang - Nurhasanah; Hadli Lidya Rikayana (Journal of Research in Business, Economics, and Education, 2021)
This study aims to explain the effect of Job Placement, Self-Efficacy, and Interpersonal Communication on Employee Performance. The population in this study were 36 employees at PT. Alima Usaha Samudera Shipyard, Kampung Bulang Tanjungpinang. Sampling with saturated technique, the sample size is 36 employees. This type of research is quantitative research. In the questionnaire, the validity and reliability were tested. Data were analyzed using multiple linear regression analysis, including t test, F test and coefficient of determination. The results showed that partially the variable Job Placement (X1), Self-Efficacy (X2), and Interpersonal Communication (X3) had a significant effect on Employee Performance. The results of the F test obtained that the F value counted 57.821 with the F table value 2.90 identified that the variable job placement, self-efficacy, and interpersonal communication simultaneously had a significant effect on the employee performance variable (Y). Based on the coefficient of determination test, about 83% of the Employee Performance variable is influenced by the Job Placement, Self-Efficacy, and Interpersonal Communication variables. The remaining 17% is influenced by other factors that are not explained in this study.